Frase Verbal Bahasa Sangil - Pareda, Herold Herbano (Kajian Linguistik, 2018)
The aims of the research are to identify the form of verb phrase in Sangil Language and to analyse its function based on the morphology and syntaxes analysis. The result of research which has been found by the researcher that verb phrase in sangil language are Mebua, wotonge metulung, mendedeno, bou kimang, kumang, kukang, metetiki, mesasinti etc.Somehow, verb phrase in sangil language has the same function with another language which consists of one up to three words but the difference can be found only in words form.Based on the data analysis verb phrase in sangil language has different form in words. It is due to sangil language has many affictations. For instance the word Mendedeno derives from the word â€œdenoâ€ which means taking a bath, after that there is a prefix â€œdeâ€which explains the event is going on, and then there is a prefix â€œmenâ€ which clings to the word dedone and becomes mendedeno. The result shows that sangil language is included agglutinative language or a language that has affix.Keywords: Verb Phrase, Sangil Language, morphology and sintaxis analysis